2009
DOI: 10.1183/09031936.00087209
|View full text |Cite
|
Sign up to set email alerts
|

Oral versus i.v. antibiotics for community-acquired pneumonia in children: a cost-minimisation analysis

Abstract: Community-acquired pneumonia represents a high financial burden to healthcare providers. This manuscript seeks to estimate and compare the costs of treating children hospitalised with community-acquired pneumonia, with oral and intravenous antibiotics, thus determining which treatment is cost minimising.A cost-minimisation analysis was undertaken alongside a randomised controlled non-blinded equivalence trial. 232 children (from eight paediatric centres in England) diagnosed with pneumonia, who required admiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 24 publications
0
34
1
Order By: Relevance
“…Some infections (for example, central nervous system infections) or patients groups (for example, neonates and infants) require parenteral use. Feleke et al (2013) reported higher administration of parentral antibiotics (81.8%) in bishoftu, Woldu et al in hawassa (93.6%), Kanish et al(92%) and Sviestina and Mozgis in lativia (64-86%).The finding in this study though relatively good, still should be discouraged and switch to oral medications when there is indication must be practiced because can reduce stay at the hospital, decrease the risk of needleborne infections like HIV/AIDS and hepatitis and can decrease administration and family-related costs (Rojas and Granados,2006;Lorgelly et al, 2010;Vouloumanou et al, 2008).…”
Section: Discussionmentioning
confidence: 61%
“…Some infections (for example, central nervous system infections) or patients groups (for example, neonates and infants) require parenteral use. Feleke et al (2013) reported higher administration of parentral antibiotics (81.8%) in bishoftu, Woldu et al in hawassa (93.6%), Kanish et al(92%) and Sviestina and Mozgis in lativia (64-86%).The finding in this study though relatively good, still should be discouraged and switch to oral medications when there is indication must be practiced because can reduce stay at the hospital, decrease the risk of needleborne infections like HIV/AIDS and hepatitis and can decrease administration and family-related costs (Rojas and Granados,2006;Lorgelly et al, 2010;Vouloumanou et al, 2008).…”
Section: Discussionmentioning
confidence: 61%
“…Alternatively, some oral antibiotics are not available on the Latvian market, e.g., flucloxacillin and penicillin Whilst some infections (e.g., central nervous system infections) or patients groups (e.g., neonates) require parenteral use there are other patient groups (e.g., children, adolescent) and/or diagnoses where the disproportionately high use of intravenous antibiotics should be reduced at hospitals in Latvia. In some situations (e.g., community acquired pneumonia or some cases of acute pyelonephritis), switch to oral antibiotics allow reducing the stay at the hospital and has potential benefits because can decrease the risk of needle-borne infections, need for referral or admission, administration costs, and family-related costs [23][24][25]. Our results are similar with the study done in pediatric antimicrobial prescribing in 32 hospitals of 21 European countries where parenteral route was more commonly used than the oral route for both prophylactic and therapeutic indications [12].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the reduction in pneumonia admissions has saved the health system US$ 3.8 million-6.1 million annually (based on United Kingdom cost-analysis data for pneumonia admissions). 31 Although modest, the additional costs owing to the increase in cases of empyema among children would be reduced by the use of a vaccine with broader pneumococcal serotype coverage. 3 In July 2011 (October 2011 in Australia's Northern Territory), Australia's 13-valent pneumococcal conjugate vaccine was introduced into the national immunization programme.…”
Section: Discussionmentioning
confidence: 99%